Low-melting-point polymeric fiber performance as drying additives for refractory castables. Issue 3 (1st February 2022) - Bezerra, B.P.; Luz, A.P.; Salomão, R.; Pandolfelli, V.C.
Abstract: Polymeric fibers can be used as drying additives for refractory compositions as their softening and decomposition at the beginning of the heating procedures of those ceramics induces the generation of permeable pathways, providing safer steam release out of the dense microstructure. Thus, it is required to select fibers that favor the preparation of castables with suitable permeability levels at temperatures as low as possible to enhance their explosion resistance during drying. Therefore, this work addresses the production of low-melting-point polymeric fibers (Tm ∼ 70–150 °C) and the evaluation of their performance when incorporated into dense high-alumina calcium aluminate cement- or hydratable alumina-bonded refractory castables. EVA (ethylene vinyl acetate copolymer), PCL (polycaprolactone) and PLA (polylactic acid) fibers were produced and added to the designed compositions. Based on the collected results, changes in fiber morphology during their softening and melting process had a great impact on the drying behavior of the castables under different heating rates. Hydratable alumina-bonded compositions were more susceptible to explosions due to such transformations, whereas the CAC-bonded ones exhibited explosion resistance at the hardest heating schedule (20 °C/min). Micrographic analysis of the fiber morphology during heating provided relevant information that helped to better understand the drying process and the permeability evolution of the evaluated dense refractory castables.